2022
DOI: 10.1155/2022/6999907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intermittent Fasting Diet on Glucose and Lipid Metabolism and Insulin Resistance in Patients with Impaired Glucose and Lipid Metabolism: A Systematic Review and Meta-Analysis

Abstract: The question of whether or not intermittent fasting diets improve the clinical indicators of glycolipid metabolism remains unclear. This study systematically reviewed the relevant clinical trials to evaluate the effects of intermittent fasting diet on glucose and lipid metabolism and insulin sensitivity in patients with metabolic syndrome. To evaluate the effect of intermittent fasting diet intervention on patients with disorders of glucose and lipid metabolism, random-effect or fixed-effect meta-analysis mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…This section also explores the experience of fasting in the final week because other studies have also proven the effects of fasting on blood sugar control. 32 Regarding the difficulty in accessing information about a healthy DM lifestyle, in this study, DM sufferers also stated that they had no difficulty obtaining information about a healthy DM lifestyle. When reviewed in more depth, most of the contents are related to the way of life of DM sufferers.…”
Section: Resultsmentioning
confidence: 63%
“…This section also explores the experience of fasting in the final week because other studies have also proven the effects of fasting on blood sugar control. 32 Regarding the difficulty in accessing information about a healthy DM lifestyle, in this study, DM sufferers also stated that they had no difficulty obtaining information about a healthy DM lifestyle. When reviewed in more depth, most of the contents are related to the way of life of DM sufferers.…”
Section: Resultsmentioning
confidence: 63%
“…10 Another systematic review and meta-analysis on fasting and T2DM found that fasting lowers BMI, insulin resistance, glycated hemoglobin levels (HbA1C), blood glucose levels, leptin, and increases adipokine concentration. 14 15 These evidences indicate a positive role of therapeutic fasting in T2DM.…”
Section: Discussionmentioning
confidence: 90%
“…Two studies found no change in weight in lean and metabolically healthy participants 22,25 . BMI decreased after IF compared to an ad libitum diet in 13 out of 14 reviews 6,11,12,15–17,20,21,23–25,27,29,30 …”
Section: Resultsmentioning
confidence: 98%
“…22,25 BMI decreased after IF compared to an ad libitum diet in 13 out of 14 reviews. 6,11,12,[15][16][17]20,21,[23][24][25]27,29,30 IF versus CER Nineteen reviews found a comparable weight loss following IF and CER. [4][5][6]11,18,19,23,[25][26][27][31][32][33][34][35][36][37][38][39] In terms of BMI change, five reviews compared IF to CER, finding no significant difference between the two interventions.…”
Section: If Versus Ad Libitummentioning
confidence: 99%
See 1 more Smart Citation